"Oh, so you just want to teach?": An Autoethnographic Account of One Traditionally Trained Teacher in a TFA-hiring School - Cook, Gretchen N.; Anderson, Ashlee B. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2023)
With this paper, we present an autoethnographic analysis of one traditionally trained teacher’s experience working in an urban charter school with predominantly TFA-trained colleagues. To begin, we provide a review of literature that highlights the research landscape’s hyper-focus on the experiences of TFA CMs, after which we describe the theoretical work that has informed this study, most notably Thomas (2018), who uses sociocultural policy studies to describe how TFA CMs embodied controversial education policies. We then outline our methodology, which we label autoethnographic counternarrative, and present our findings/analysis, focusing on the following thematic elements: 1) Just being a teacher and 2) Psychology of novice teachers. To conclude, we discuss various implications of this work for teacher education, as well as the teaching profession at large, paying particular attention to the ways in which neoliberal education reforms, including TFA, effectively incentivize the individualization of teaching (and learning).